Il catechismo ritrovato: Ottavio Iezzo e il più antico "Fiore della dottrina cristiana" in greco volgare (Roma 1576) - Pontani, Filippomaria (Orientalia christiana periodica, 2024)
The earliest modern Greek version of the Catholic catechism, the Anthos tes christianikes didaskalias, is preserved in the single extant copy (now kept in the Biblioteca Angelica in Rome) of a book published in 1576 by Francesco Zanetti. Realised by Ottavio Iezzo, a member of the Greek community of Naples, this hitherto almost unnoticed text deserves closer study not only for its linguistic facies, for the only illustration it carries (Abraham and the Holy Trinity), and for the problem of its sources (several Latin and Italian catechisms or Tabulae christianae religionis can be compared with it), but above all as a token of the Roman interest for the spreading of the Catholic faith in the Greek-speaking East as well as in the Greek communities of Southern Italy - most importantly, in the very same year 1576 pope Gregory XIII establishes the Collegio greco di Sant'Atanasio. The paper attempts to tackle these issues and presents the first full transcription of the Anthos.